Dietary supplementation with chestnut (Castanea sativa) reduces abdominal adiposity in FVB/n mice: a preliminary study - Rodrigues, Pedro (2018)
The production of chestnut (Castanea sativa Miller) is mostly concentrated in Europe. Chestnut is recognized by its high content of antioxidants and phytosterols. This work aimed to evaluate the e ects of dietary chestnut consumption over physiological variables of FVB/n mice. Eighteen FVB/n male 7-month-old mice were randomly divided into three experimental groups (n = 6): 1 (control group) fed a standard diet; 2 fed a diet supplemented with 0.55% (w/w) chestnut; and 3 supplemented with 1.1% (w/w) chestnut. Body weight, water, and food intake were recorded weekly. Following 35 days of supplementation, the mice were sacrificed for the collection of biological samples. Chestnut supplementation at 1.1% reduced abdominal adipose tissue. Lower serum cholesterol was also observed in animals supplemented with chestnut. There were no significant di erences concerning the incidence of histological lesions nor in biochemical markers of hepatic damage and oxidative stress. These results suggest that chestnut supplementation may contribute to regulate adipose tissue deposition.